1976
DOI: 10.2113/gsecongeo.71.8.1507
|View full text |Cite
|
Sign up to set email alerts
|

Lineaments; ineffective guides to ore deposits

Abstract: For many years some geologists have been much impressed by real or imagined linear arrangements of various geologic features: drainage lines, faults, joints, volcanoes, ore deposits, and even anticlines. Such real or fancied lineaments have commonly been attributed to deep-seated wrench (strike-slip) faults. Some seem to regard the San Andreas fault as typical; others refer to zones as much as 100 miles wide as lineaments, but surely no one would suggest that a zone that wide would be a guide to ore. In this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1979
1979
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 6 publications
0
2
0
1
Order By: Relevance
“…The availability of high quality earth imagery has also provided an impetus to the recognition and interpretation of continental lineaments (e.g., Norman 1980). Although many of these efforts do not stand upwell to scrutiny (see Gilluly 1976), the whole question of the possible significance of deep crustal flaws to certain groups of metal deposits cannot be summarily dismissed. Sykes (1978Sykes ( , 1980 has demonstrated that the reactivation of zones of weakness in continental crust can be related to the development of transform faults in nascent ocean basins, and that these zones tend to control sites of intracontinental alkaline magmatism in west Africa and elsewhere (see also Marsh 1973;Culver and Williams 1979).…”
Section: Lineaments and Metal Depositsmentioning
confidence: 99%
“…The availability of high quality earth imagery has also provided an impetus to the recognition and interpretation of continental lineaments (e.g., Norman 1980). Although many of these efforts do not stand upwell to scrutiny (see Gilluly 1976), the whole question of the possible significance of deep crustal flaws to certain groups of metal deposits cannot be summarily dismissed. Sykes (1978Sykes ( , 1980 has demonstrated that the reactivation of zones of weakness in continental crust can be related to the development of transform faults in nascent ocean basins, and that these zones tend to control sites of intracontinental alkaline magmatism in west Africa and elsewhere (see also Marsh 1973;Culver and Williams 1979).…”
Section: Lineaments and Metal Depositsmentioning
confidence: 99%
“…Vale destacar que, embora bastante eficazes em mapeamentos geológicos de áreas com grandes dimensões, a extração de lineamentos estruturais a partir de imagens de radar exige certo rigor técnico, a fim de evitar a geração de informação espúria, derivada de uma interpretação equivocada da estrutura/alvo analisado ou sem qualquer significado geológico (Gilluly, 1976;O'Leary, 1976;Kellndorfer et al, 2004). Dessa forma, os fotolineamentos mais visíveis e com dimensões apreciáveis foram identificados e mapeados utilizando o software ArcMap 10.1.…”
Section: Análise De Macroestruturas Em Produtos De Sensores Remotosunclassified
“…improvements in spectral and spatial resolution of a sensor, refinements to corrections for attenuation or development of a new algorithm to enhClnce contrasts. Geologists and geophysicists com identify needs related to characteristic spectral radiances for rocks or better understanding of the ubiquitous lineal'S which have well publicized, but poorly defined, relationships to ore (c. f. Carter et aI., 1977;Gilluly, 1976).…”
Section: Technical Challengesmentioning
confidence: 99%